Growing bell pepper the environment-friendly way - Sardana, H R; Bhat, M N (Indian Horticulture, 2015)
Area-wide validation and promotion of IPM technology in bell pepper resulted in reduced number of chemical sprays and cost of cultivation with increased profit margins. Successful implementation of IPM has created awareness among farmers about the demerits of using excessive chemical pesticides. Consequently, a large number of farmers are coming forward to implement IPM technology in bell pepper.